RISK ASSESSMENT FOR RADON EXPOSURE IN VARIOUS INDOOR ENVIRONMENTS - Chen, Jing (Radiation protection dosimetry, 2019)
Using data from a number of radon surveys, it was assessed that on average, radon progeny concentrations in Canadian homes are about three times higher than in school buildings, 4.7 times higher than in public buildings and indoor workplaces, and 12 times higher than in outdoor air. Canadian statistics show that most Canadians spend ~70% of their time indoors at home, 20% indoors away from home and 10% in outdoors. Due to relatively higher radon concentration in residential homes and longer time spent indoors at home, the exposure at home contributes to 90% of the radon-induced lung-cancer risk.